PENGAPLIKASIAN KOMPOS AMPAS TAHU DAN ENDAPAN EFFLUENT PADA TANAH ULTISOL UNTUK PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Lukita, Andreas; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to determine the effect of tofu waste compost and effluent precipitate on the growth of oil palm seedlings (Elaeis guineensis Jacq.) and to determine the precise dose Ultisol soil in the main nursery. This research was conducted at the experimental station of Agriculture Faculty, University of Riau on February to May 2016. This research was arranged on using Completely Rendomized Design (CDR) with two factorial. Factor I is application of tofu waste compost : A0 (without tofu waste compost), A1 (10 tons/ha), A2 (20 tons/ha), A3 (30 tons/ha). Factor II is application effluent precipitate : E0 (without effluent precipitate), E1 (15 tons/ha), E2 (30 tons/ha), E3 (45 tons/ha) and replicated 3 times, so obtained 48 unit experiment. Parameter observed were the accretion of plant heigh, accretion of leaves number, accretion of stump diameter, root volume, root shoot ratio and dry weight. The result showed that giving tofu waste compost dose 10 tons/ha and effluent precipitate 45 tons/ha give the best effect on the growth of oil palm in main nursery. The giving tofu waste compost increase accretion of plant heigh, accretion of leaves number, root volume and dry weight with get the best dose 10 tons/ha. The giving effluent precipitate the increase accretion of leaves number, accretion of stump diameter, root volume and dry weight with get the best dose 45 tons/ha. Keywords: Oil palm seedling, Tofu waste compost, Effluent precipitate,Ultisol soil